Pengaruh Model Pembelajaran Project Based Learning terhadap Hasil Belajar Mata Pelajaran Informatika Kelas IX SMP Islam Al-Fattahiyyah - Muhamad Faj’rurosyad; Vertika Panggayuh (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
In the rapidly evolving digital era, informatics education plays a crucial role in equipping students with 21st-century competencies. However, at SMP Islam Al-Fattahiyyah, Grade IX students show low interest and achievement in this subject, with most failing to meet the Minimum Mastery Criteria (KKM). This situation prompted research to examine the effectiveness of the Project-Based Learning (PjBL) model as an alternative instructional approach emphasizing student activity, collaboration, and contextual material application. The main objective of this study is to determine the extent of PjBL’s influence on student learning outcomes. The research employed a quantitative method with an associative design, involving 140 students from a total population of 215 through simple random sampling. Data were collected using questionnaires and documentation of midterm exam scores. Statistical analysis revealed a t-value of 4.743 with a significance level of 0.000 (< 0.05), indicating a significant effect. Most students expressed a positive perception of this learning model. These findings confirm that PjBL not only enhances cognitive abilities but also enriches students’ learning experiences in a more meaningful way.